“Whatever happens, happens” challenges of end-of-life communication from the perspective of older adults and family caregivers: a Qualitative study - Im, Jennifer (BMC Palliat Care, 2019)
BACKGROUND: Effective communication is integral to the delivery of goal-concordant care for older adults and their family caregivers, and yet, it is uncommon in people with serious illness. This study explores the challenges of integrating end-of-life communication into heart failure management from the perspectives of older adults and family caregivers. METHODS: In a qualitative study of older adults with heart failure and their family caregivers, fourteen semi-structured interviews were conducted with 19 participants in Ontario, Canada. The interviews were transcribed verbatim and thematic analysis was applied to analyze the data. RESULTS: Four themes were identified in the context of participants’ understanding of illness: 1) trivializing illness-related challenges, 2) positivity in late life, 3) discomfort in having end-of-life conversations, and 4) reluctant to engage despite need. These challenges often intertwine with one another. Most participants had not engaged in end-of-life discussions with their clinicians or family members. CONCLUSION: The findings provide insights that can inform approaches to integrate end-of-life communication for older adults with serious illness and caregivers. The identified challenges highlight a need for end-of-life communication to occur earlier in illness to be able to support individuals throughout the period of decline. In addition, end-of-life communication should be introduced iteratively for those who may not be ready to engage. Alternative approaches to communication are needed to elicit the challenges that patients and caregivers experience throughout the progression of illness to improve care for people nearing the end of life.